Thermo-mechanical stress analysis of the turbine of helicopter engine - Lucjan Witek; Feliks Stachowicz (Advances in Mechanical and Materials Engineering, 1970)
In this paper the results of the numerical stress analysis of the power turbine of helicopter engine were presented. In order to solve the problem, the nonlinear finite element method was used. The numerical models of both the blade and the disc segment were made using the MSC-Patran program. In the analysis the thermal load resulting from non-uniform temperature field was defined. The centrifugal force resulting from the rotation of the engine rotor was also considered. The cyclic symmetry boundary condition of the disc segment was used to decrease the size of the numerical task. The model of the turbine material was defined as linear-elastic. The modulus of elasticity and the thermal expansion coefficient of the disc and the blade material were considered as temperature dependent. As a result of performed computations, the stress distributions for the turbine subjected to both the thermal and the mechanical loads were determined.